STRATEGI PENGEMBANGAN KAPASITAS PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) SEBAGAI PENYEDIA LAYANAN BIDANG PENDIDIKAN - Tohani, Entoh (Jurnal Penelitian Ilmu Pendidikan, 2015)
Community Learning Center (CLC) as educational service provider ideally can do its functions optimum to develops and mediates community to their invorirentment. CLC have to make improvements on aspects of organization management through impelementation of various strategies of capacity development. Because of these, the research done. The research subject is eight PKBM in Bantul, Province of The Special Region of Yogyakarta. determined by purposive. Gathering and analysis of data done qualitatively, while authenticity technique of data with triangulation and college discussion. The result of research shows that implementation of strategies of capacity development on program, educational process, facility, external enviorenment, personnel, and partnership done by the CLCs are in standar or implementing level. If s means that the creative, inovatif and holistic ways of the strategies are not optimum. Also, there are constraints faced by the CLCs on gains their goal includes personnel, geographical position, and perception local government to CLC. Thereby, for continuing development of CLC required an idea and action guarantying expansion of CLC in integrated and totally, and accompanied by professional behavior of the personnel. Key words: Community Learning Center (CLC), Development, Strategy, Capacity